Regioselective Hetero-Michael Addition of Oxygen, Sulfur, and Nitrogen Nucleophiles to Maleimides Catalyzed by BF3·OEt2 - An, Yu-Long; Deng, Yun-Xia; Zhang, Wei; Zhao, Sheng-Yin (Synthesis, 2015)
A practical BF3·OEt2-catalyzed regioselective 1,2-addition or 1,4-hetero-Michael addition of oxygen, sulfur, and nitrogen nucleophiles to maleimides has been developed for the synthesis of alkyl fumarate derivatives or 3-substituted succinimides, respectively. This reaction system has wide substrate scope and gives moderate to excellent yields (up to 96%) of the desired products. In contrast to the base-catalyzed methods, this strategy is very general, simple, environmentally friendly, and tolerant of oxygen.
Keywords: Michael addition; maleimide; oxygen nucleophiles; sulfur nucleophiles; nitrogen nucleophiles; boron trifluoride diethyl etherate